DETERMINAN CADANGAN DEVISA DI 5 NEGARA ASEAN PASCA GEJOLAK EKONOMI COVID-19 - Ambarwati, Dwi; Oktavilia, Shanty (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study examines the macroeconomic factors influencing foreign exchange reserves in five ASEAN countries (Indonesia, Malaysia, Thailand, Vietnam, and the Philippines) during the 2022–2024 period, in the aftermath of the COVID-19 pandemic and rising global interest rates. A panel data regression using the Fixed Effect Model (FEM) was employed. Independent variables include exports, imports, exchange rates, inflation, benchmark interest rates, and foreign direct investment (FDI), with foreign exchange reserves as the dependent variable. Results show that all variables have significant effects. Imports, exchange rates, interest rates, inflation, and FDI contribute to the increase in reserves, while exports have a negative impact. This suggests that heavy reliance on imported raw materials reduces the positive contribution of exports. Policy implications include strengthening export structures, managing productive imports, stabilizing exchange rates, controlling inflation, and enhancing the quality of FDI. The findings offer empirical insights for external resilience strategies in the ASEAN region.